2011
DOI: 10.1016/j.jacc.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Association of Annular Calcification and Aortic Valve Sclerosis With Brain Findings on Magnetic Resonance Imaging in Community Dwelling Older Adults

Abstract: Objective The objective of this study is to investigate the association of mitral annular calcification (MAC), aortic annular calcification (AAC), and aortic valve sclerosis (AVSc) with covert magnetic resonance imaging (MRI)-defined brain infarcts. Background Clinically silent brain infarcts defined by MRI are associated with increased risk of cognitive decline, dementia, and future overt stroke. Left sided cardiac valvular / annular calcifications are suspected as risk factors for clinical ischemic stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 39 publications
4
36
0
2
Order By: Relevance
“…Two of the other 3 population-based studies did not reveal a significant association between mitral annular calcification and risk for ischemic stroke in adjusted analyses. 503,506 No association was observed among 568 patients assigned to placebo in an AF trial. 512 Mitral annular calcification is associated with cardiovascular risk factors and atherosclerosis in other vascular distributions.…”
Section: Mitral Annular Calcificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the other 3 population-based studies did not reveal a significant association between mitral annular calcification and risk for ischemic stroke in adjusted analyses. 503,506 No association was observed among 568 patients assigned to placebo in an AF trial. 512 Mitral annular calcification is associated with cardiovascular risk factors and atherosclerosis in other vascular distributions.…”
Section: Mitral Annular Calcificationmentioning
confidence: 99%
“…Idiopathic calcification of the mitral valve is common in the general population [503][504][505][506][507][508] and is detected on ultrasonography in ≥10% of patients with TIA or ischemic stroke. 509, 510 The condition affects women more than men and is strongly associated with age.…”
Section: Mitral Annular Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodriguez et al 19 revealed that left sided cardiac valvular calcifications were associated with covert MRI-defined brain infarcts. Vascular calcification is a well-known complication of CKD but results revealed no significant association between aortic valve calcification and CKD in this study.…”
Section: Discussionmentioning
confidence: 99%
“…40, 41 Diseases of the aortic valve, including aortic regurgitation, stenosis, sclerosis, and annular calcification, do not appear to independently increase the risk of IS. 42 Valve replacement increases the risk of IS via thromboembolism and this risk is greater with mechanical than bioprosthetic valves. Most patients with mechanical valves should be treated with warfarin and aspirin, with a target INR of 2.0-3.0 for low-risk aortic valve patients, or of 2.5-3.5 for patients with additional risk factors or mitral valves.…”
Section: Valvular Heart Diseasementioning
confidence: 99%